2020
DOI: 10.3389/fneur.2020.00736
|View full text |Cite
|
Sign up to set email alerts
|

The Neurology of Death and the Dying Brain: A Pictorial Essay

Abstract: As neurologists earn their living with the preservation and restoration of brain function, they are also well-positioned to address the science behind the transition from life to death. This essay in pictures highlights areas of neurological expertise needed for brain death determination; shows pitfalls to avoid during the clinical examination and interpretation of confirmatory laboratory tests in brain death protocols; illustrates the great variability of brain death legislations around the world; discusses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 97 publications
(160 reference statements)
0
15
0
1
Order By: Relevance
“… 86 One of us therefore recently suggested that terminal CSDs are a phylogenetically preserved mechanism which must have occurred in the last common ancestor of humans and insects for over 500 million years ago. 14 CSDs might therefore be conceivable as an underlying mechanism for both NDE and thanatosis. Indeed, migraine aura (which is caused by CSDs) was a predictor of NDE in a crowdsourcing study 13 of unprimed lay people adjusted for age and sex (OR 2.33, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 86 One of us therefore recently suggested that terminal CSDs are a phylogenetically preserved mechanism which must have occurred in the last common ancestor of humans and insects for over 500 million years ago. 14 CSDs might therefore be conceivable as an underlying mechanism for both NDE and thanatosis. Indeed, migraine aura (which is caused by CSDs) was a predictor of NDE in a crowdsourcing study 13 of unprimed lay people adjusted for age and sex (OR 2.33, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from all these candidate mechanisms has been combined into a ‘diathesis-stress model’. 11 , 14 , 101 Thus, an unusually sensitive arousal system (i.e. the diathesis), as revealed by REM sleep intrusion, would predispose people to NDE in life-threatening situations and emotional stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain death is defined as the complete and permanent absence of all brain functions ( Busl and Greer, 2009 ). Protocols for ascertaining brain death vary widely from country to country ( Kondziella, 2020 ). In Italy, a patient is considered brain dead when he is in a coma, showing apnoea under particular clinical parameters, and having no brain stem reflexes ( Legge, 1993 , Decreto Ministero della Salute 11 Aprile 2008 ).…”
Section: Introductionmentioning
confidence: 99%